2010
DOI: 10.3171/2010.3.spine09887
|View full text |Cite
|
Sign up to set email alerts
|

Using the T2-weighted magnetic resonance imaging signal intensity ratio and clinical manifestations to assess the prognosis of patients with cervical ossification of the posterior longitudinal ligament

Abstract: Patients with low signal intensity ratios that changed on T2-weighted imaging experienced a good surgical outcome. Low increased signal intensity might reflect mild neuropathological alteration in the spinal cord and greater recuperative potential. An increased signal intensity ratio with positive pyramidal signs indicates less recuperative potential of the spinal cord and a poor surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…In case of Japan, some authors had concluded that patient age influences on the clinical outcome of the laminoplasty5,22). In this study, although preoperative modified JOA score was statistically same between the elderly group and the non-elderly group, postoperative modified JOA score was different between the two groups.…”
Section: Discussionmentioning
confidence: 48%
“…In case of Japan, some authors had concluded that patient age influences on the clinical outcome of the laminoplasty5,22). In this study, although preoperative modified JOA score was statistically same between the elderly group and the non-elderly group, postoperative modified JOA score was different between the two groups.…”
Section: Discussionmentioning
confidence: 48%
“…Since that report, a few studies [1013] have focused on the quantitative assessment of SI changes and their prognostic significance. Most of these studies assessed the SI of the spinal cord based on T2WI alone, but not on T1WI and gadolinium-diethylenetriaminepentaacetic acid (Gd-DTPA) contrast-enhanced MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced continuous OPLL may demonstrate the development of a Haversian canal system within the calcified ligament. 5 Wang et al 34 studied T2 signal intensity ratios between intramedullary areas posterior to compressive ossified PLL compared with the intramedullary signal behind the C7-T1 disc space where there was no compression in patients with myelopathy prior to laminoplasty. They concluded that patients with low signal-intensity ratios had better surgical outcomes than those with high signal-intensity ratios and evidence of pyramidal signs.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that patients with low signal-intensity ratios had better surgical outcomes than those with high signal-intensity ratios and evidence of pyramidal signs. 34 Given the likely progression of untreated OPLL we advocate for early surgical intervention.…”
Section: Discussionmentioning
confidence: 99%